No language left behind? Towards an integrated framework for linguistic rights, human rights and technology regulation - Birnie, Ingeborg (Language and Law / Linguagem e Direito, 2026)
This paper explores the intersection of artificial intelligence (AI) governance and linguistic diversity, focussing on the digital challenges minority and endangered languages face. It presents a novel framework that applies the lifecycle of digital systems—input, process, and output—to analyse the barriers faced by these languages in AI technologies. Through this lens, it critically examines existing international and European legal instruments, revealing a significant policy gap in addressing the explicit inclusion of minority languages in digital and AI domains. The paper’s key contribution lies in its proposal for an integrated, multi-framework approach that combines human rights, minority language protection, and AI governance to ensure equitable linguistic representation. It argues that without urgent and coordinated action, many languages risk digital extinction, with profound implications for cultural identity and access to information. This work calls for comprehensive regulatory reform to secure a digitally inclusive future for all linguistic communities.